Critical Structure for Telescopic Movement of Honey bee (Insecta: Apidae) Abdomen: Folded Intersegmental Membrane. Issue 1 (25th July 2016) - Zhao, Jieliang; Yan, Shaoze; Wu, Jianing
Abstract: The folded intersegmental membrane is a structure that interconnects two adjacent abdominal segments; this structure is distributed in the segments of the honey bee abdomen. The morphology of the folded intersegmental membrane has already been documented. However, the ultrastructure of the intersegmental membrane and its assistive role in the telescopic movements of the honey bee abdomen are poorly understood. To explore the morphology and ultrastructure of the folded intersegmental membrane in the honey bee abdomen, frozen sections were analyzed under a scanning electron microscope. The intersegmental membrane between two adjacent terga has a Z–S configuration that greatly influences the daily physical activities of the honey bee abdomen. The dorsal intersegmental membrane is 2 times thicker than the ventral one, leading to asymmetric abdominal motion. Honey bee abdominal movements were recorded using a high-speed camera and through phase-contrast computed tomography. These movements conformed to the structural features of the folded intersegmental membrane.